2021
DOI: 10.3390/app11209714
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fine Crack Images Using Image Processing Technique and High-Resolution Camera

Abstract: Visual inspections are performed to investigate cracks in concrete infrastructure. These activities require manpower or equipment such as articulated ladders. Additionally, there are health and safety issues because some structures have low accessibility. To deal with these problems, crack measurement with digital images and digital image processing (DIP) techniques have been adopted in various studies. The objective of this experimental study is to evaluate the optical limit of digital camera lenses as workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In turn, article [2] is devoted to the identification of cracks in concrete. The work associated with this kind of research requires effort and equipment, such as articulated ladders.…”
Section: Research In the Field Of New And Improved Methods And Techni...mentioning
confidence: 99%
“…In turn, article [2] is devoted to the identification of cracks in concrete. The work associated with this kind of research requires effort and equipment, such as articulated ladders.…”
Section: Research In the Field Of New And Improved Methods And Techni...mentioning
confidence: 99%
“…Although many studies have successfully measured concrete crack width by using pixels, this unit of measurement remains a significant limitation: this is because determining the width of concrete cracks in pixels does not provide practical information for field applications, as the severity of concrete crack width is better understood in millimetres. Some studies [36][37][38][39][40][41] have found ways to measure concrete crack width in millimetres by devising methods to carry out pixel to millimetre conversion. However, Nyathi et al [5] found that these methods require knowledge of key parameters that may not always be readily available, such as focal length, camera resolution, number of pixels along the long side of image sensor, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Jeong et al [29] used Otsu image processing to measure crack width in pixels. The crack width was converted to millimeters using a proposed equation shown in Equation (3).…”
Section: Introductionmentioning
confidence: 99%